Critical theory, justice and metaphilosophy: validation of political philosophy in Fraser and Honneth [Spanish] (2012)
When talking about justice and injustice, can philosophers, simply, take the victims’ side? Even when these philosophers belong to the critical theoretical tradition, can they be excused from providing an objective account of what is morally wrong? If, for instance, they hold that what victims are demanding is recognition instead of redistribution, shouldn’t they provide a convincing theory of recognition and the role it plays in situations of justice and injustice? Contrasting the theories of Iris Marion Young, Nancy Fraser and Axel Honneth, three philosophers who establish a link between recognition and justice and who subscribe to the critical theory’s tradition, this article tries to explain their differences. In fact they go in different directions when they have to explain how recognition is involved in social conflicts and in political demands. The paper´s purpose is to show that their differences have to do, mainly, with two different understandings of political philosophy as an intellectual enterprise.